1993
DOI: 10.1111/j.1439-0450.1993.tb00180.x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Infection with Yersinia Pseudotuberculosis of Ground Squirrels (Citellus Citellus)

Abstract: Summary An experimental infection was induced in the European ground squirrel (Citellus citellus) by intraperitoneally injecting of 1 ml. of microbial suspension, containing 1 times 109 CFU (colony forming units) of Yersinia pseudotuberculosis, serotypes I and III. The infectious process was dynamically followed up from the 1st up to the 30th day, respectively. Account was rendered to the general condition, the internal body temperature and the mortality rate. The phagocytic activity of alveolar macrophages (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
(4 reference statements)
1
4
0
Order By: Relevance
“…Other studies (Logsdon and Mecsas, 2003) revealed that a yopH mutant of Y. pseudotuberculosis also fails to colonize the MLN at orogastrical murine model. Moreover, Balada‐Llasat and Mecsas (2006) reported lymphadenitis with multiple necrotic foci in MLN at intragastral infection of mice, similarly to our previous investigation on ground squirrels (Veljanov et al., 1993), where small necrotic and necrobiotic foci were found in liver, spleen and MLN. Surprisingly, no morphological changes were detected 2–4 weeks after intraperitoneal infection of ground squirrels with Y. pseudotuberculosis serotype O:1.…”
Section: Discussionsupporting
confidence: 85%
“…Other studies (Logsdon and Mecsas, 2003) revealed that a yopH mutant of Y. pseudotuberculosis also fails to colonize the MLN at orogastrical murine model. Moreover, Balada‐Llasat and Mecsas (2006) reported lymphadenitis with multiple necrotic foci in MLN at intragastral infection of mice, similarly to our previous investigation on ground squirrels (Veljanov et al., 1993), where small necrotic and necrobiotic foci were found in liver, spleen and MLN. Surprisingly, no morphological changes were detected 2–4 weeks after intraperitoneal infection of ground squirrels with Y. pseudotuberculosis serotype O:1.…”
Section: Discussionsupporting
confidence: 85%
“…All animals were killed during winter hunting and probably our ®ndings represent latent infections, when bacterial cells are disseminated by the blood and lymph routes to the viscera. Bacterial dissemination to the viscera was shown in our earlier investigations of experimental Yersinia infection (Veljanov et al, 1993;Markova et al, 1994;Nikolova and Vesselinova, 1995;Nikolova et al, 1997;Najdenski et al, 1998).…”
Section: Discussionmentioning
confidence: 68%
“…Evidently, rats are quite resistant to Y. pseudotuberculosis infection, in contrast to European ground squirrels which are more sensitive and i.p. challenge of 1.0 · 10 9 CFU caused lethal infection within a week (Veljanov et al, 1993). Histological examinations of rabbits infected with both wild-type and mutant Y. pseudotuberculosis strains showed the same changes in viscera as to those found in the ground squirrel model (Veljanov et al, 1993).…”
mentioning
confidence: 61%
“…Evidently, rats are quite resistant to Y. pseudotuberculosis infection, in contrast to European ground squirrels which are more sensitive and i.p. challenge of 1.0 × 10 9 CFU caused lethal infection within a week (Veljanov et al., 1993).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation